Panoramic radiography versus reformatted dental computed tomography for implant site analysis in maxillary edentulous posterior region` - Noha Ossama Abdelaziz Issa; Hossam Ahmed Kandil; Mohamed Mohamed Elsorougi; Samir Abdelmoneim Eltatawy (Cairo : Noha Ossama Abdelaziz Issa, 2008)
In the past years,there has been an increasing demand for the use of endosseous implants as a replacement for missing teeth. The key to success of any surgical implant procedure is the accurate and proper preoperative planning.Fiteen patients of both sexes at an age range between 53 and 67 years were selected for this study
Thesis (M.Sc.) - Cairo University - Faculty of Oral and Dental Medicine - Department of Oral-Radiology
Issued also as CD
Keywords: Dental Computed Tomography; Implant site; Panoramic